Opportunistic infections changed before and after SARS-CoV-2 infection in inflammatory bowel disease patients: a retrospective single-center study in China - Fan, Zhenzhen; Zhou, He; Zhang, Jiaqi; Liu, Xiaoning; Wu, Tong; Shi, Yanting; Lin, Junchao; Liang, Jie (Frontiers in Medicine, 2024)
Objective: SARS-CoV-2 transmission has become a serious worldwide public health concern.However, there is currently insufficient data to determine whether SARS-CoV-2 infection would affect opportunistic infections in inflammatory bowel disease (IBD) patients.Methods: A retrospective study included 451 IBD patients (294 UC and 157 CD). The IBD patients were divided into two groups: before SARS-CoV-2 infection and after SARS-CoV-2 infection, and outcomes were measured for these groups. The primary outcome was the presence and distribution of opportunistic infections. The secondary outcomes included factors associated with opportunistic infections, based on which a nomogram prediction model was developed and validated.Results: After SARS-CoV-2 infection, the proportion of IBD patients with opportunistic infections by Clostridium difficile (21.31% vs. 14.01%, p = 0.044) and Epstein-Barr virus (13.93% vs. 4.35%, p = 0.001) was significantly higher compared to that before. Conversely, the proportion of patients with hepatitis B virus (3.69% vs. 10.14%, p = 0.006) and herpes simplex virus type Ⅰ (1.23% vs. 4.35%, p = 0.04) infections was significantly lower after the infection. Additionally, pre-SARS-CoV-2 infection factors associated with opportunistic infections in IBD include duration of illness, red blood cell count, the presence of comorbid chronic illnesses, and alcohol consumption, while post-SARS-CoV-2 infection, the primary risk factors involve corticosteroid use, red blood cell count, protein level, and high-sensitivity C-reactive protein.After the SARS-CoV-2 infection, there has been a shift in the occurrence of opportunistic infections among IBD patients. It might be attributed to the use of corticosteroids and also the strengthening of containment measures, heightened public health awareness, and widespread vaccination.